HiGame: Improving elderly well-being through horticultural interaction - Wu, Y.; Chang, T.; Datta, Sambit (Multi-Science Publishing Co. Ltd, 2016)
Family support is the key to the well-being problems of elderly. Unlike health problem, mental problem often depends on the social network of elderly. How to enhance elderly well-being problems will become how to increase the interaction between elderly and their family. Horticultural interaction proves to be an effective but smooth impact on improving well-being problems of elderly. By designing a horticultural interaction game for motivating or invoking the communication between elderly and their family members, the prototype is developed based on the framework of behavior setting and semi-fixed features. Three groups of games, physical games, virtual games, and spatial interaction games, are analyzed and 14 cases are studied and evaluated for the features required. Particularly, spatial interaction games with both physical and virtual games are brought into scope, and HiGame (Horticultural Interaction Game, hi game) is developed. Five scenarios using sensor network and mobile interface are unleashed and tested in an experiment with two sets of elderly family participants. HiGame has connection to both physical and virtual spaces for elderly and their family. Elderly interact with distant family through physical watering, weeding, and fertilizing. And distant family use virtual game to support elderly. The interaction process can be further enhanced with the following: (1) separating the tasks for elderly and family ends individually and then cooperating together might enforce the intergenerational interaction and reflection on cooperation in the gaming process; (2) the connection among each scenario can be further developed into a different process, such as competition of different members for helping the elderly to complete certain task might motivate the game experience further.